Teaching as an object of representation: an approach based on the theory of social representations - Peña Vargas, Carmen Silvia; Meza Romero, Juan Carlos; Escalante Ferrer, Ana Esther (Cultura y Representaciones Sociales, 2019)
In this article we intend to highlight the relevance of the theory of social representations as a theoretical-methodological corpus for studying teaching in relation to a complex, multidimensional and subjective activity, involving multiple actions associated with the teaching-learning process and going beyond the context of the school and classroom. The discussion is conceptually based on the theory of social representations. This research has a theoretical-conceptual framework style developed in two phases: the first one involved searching documents contained in various collections under the headings of teaching and social representations. The second one constitutes the central objective of this article, which is to build an argument around the pertinence and validity of the theory of social representations and thereby recognize the meanings that teachers build relating to their work arising from the convergence of the cognition, social and affective processes mediated by the flow of experiences offered by daily practices.